Jewban Diaspora Narratives on Identity, Belonging, Resilience, Privilege and Community (In Factis Pax: Journal of Peace Education and Social Justice, 2024)
Immigration, migration, and diasporas are growing areas of study for scholars of peace and conflict. Such studies address reasons for migration and displacement, the experience of emigrating, treatment of immigrants, relevant policies and more (See, for example, Toivanen & Baser, 2020; Vertovec, 2005). Cuban American Jews, or Jewbans, as they are called (and call themselves), are a unique diaspora.  They reside in many places in the US, although South Florida is home to the largest group. On the large, the Jewbans are a highly successful demographic in Miami and other locations. Many factors contribute to this success and are part of Jewbans’ narratives that have been passed down intergenerationally. Other factors, however, do not seem to be part of Jewbans’ narratives yet may be equally relevant to their success. As much research has shown, immigrant narratives shape how subsequent generations identify, socially, economically, and politically. This in turn is connected to how and in what ways they build community.  This paper begins with a brief discussion of the Jewban diaspora, emphasizing key milestones and timelines. It focuses largely on the wave of Jewbans known as exiles and their families who were raised in South Florida. The paper then highlights themes related by one family of Jewbans, most of whom currently live in South Florida and all of whom lived there for many years. I am a participant researcher, as the family that I interviewed are all members of my husband’s immediate or extended family.  Although much has been written about the Jewbans, most was authored by persons who are themselves Jewban. I am not Jewish nor Cuban. Further, this paper adds to the literature about the Jewban experience by identifying themes that emerged across three different generations related to identity, belonging, resilience, privilege, and community.
Keywords: Identity; Belonging; Community; Privilege; Jewban Diaspora